PROTOTYPING A HEAT RECOVERY VENTILATION SYSTEM - Bilal Tlais Hussein; Radu Tarca; Daniel Anton; Dan Craciun (Nonconventional Technologies Review)
This paper presents the, prototyping, and assembly process of a novel Heat Recovery Ventilation System (HRVS) in order to increase the indoor air quality (IAQ) without consumption energy. This HRVS plays the role of heat transfer between hot and cold air with high efficiency confirming thermal comfort. Out of careful prototyping and assembly techniques, an efficient HRVS unit have developed that can be introduced in residential buildings in a compact size. This paper discusses the 3D printing of the components, including heat exchangers and air distributer with PLA material. In addition, installing the fans and the control system to achieve comfort behaviour ventilation without energy cost. Moreover, the performance of the HRVS will be tested in order to assess the real-world environments.